Knowledge Level Analysis of Pre-Service Biology Teacher on Fact and Myth Down Syndrome - Iseu Laelasari; Alfika Auliana; Sauki Fadlillah Nurus Sobah (Department of Biology Education, Faculty of Education and teacher Training, Maritime University of Raja Ali Haji, 2021)
Down syndrome is a genetic disorder caused by